About Epistemic Negation and World Views in Epistemic Logic Programs. Issue 5 (September 2019) - COSTANTINI, STEFANIA
Abstract: In this paper we consider Epistemic Logic Programs, which extend Answer Set Programming (ASP) with " epistemic operators" and " epistemic negation", and a recent approach to the semantics of such programs in terms of World Views . We propose some observations on the existence and number of world views. We show how to exploit an extended ASP semantics in order to: (i) provide a characterization of world views, different from existing ones; (ii) query world views and query the whole set of world views.